The Effectiveness of Subdistrict Head Leadership in Increasing Community Participation in Nanggalo Subdistrict, Padang City - Edja Suci Ramadhani; Naya Putri Nasywa; Raisya Syakira; Indri Ramadhani Putri; Mulyati Rahmah; Nuriwa Putri Utami; Nizrina Wulandari Ayunda; Syamsir Syamsir (JURNAL PENDIDIKAN IPS, 2026)
Although the government has provided various participatory forums at the subdistrict level, community involvement in development planning and evaluation remains relatively low. Previous research has generally focused on the role of subdistrict heads in improving bureaucratic performance and public services, while studies on the effectiveness of participatory leadership in increasing community participation remain limited. This study aims to analyze the effectiveness of the Nanggalo Subdistrict Head’s leadership in increasing community participation and to identify the strategies, dynamics, and barriers that influence residents’ involvement in development. The study employs a qualitative approach with an interpretive paradigm through a single-case holistic case study design in Nanggalo Subdistrict, Padang City. Data were collected through in-depth interviews, observations, and document analysis involving the subdistrict head, subdistrict officials, community leaders, and residents selected through purposive sampling. Analysis was conducted interactively through data reduction, data presentation, and drawing conclusions. The results indicate that the effectiveness of the sub district head’s leadership is determined by the ability to establish dialogic communication, facilitate collaboration, and strengthen public trust. Community participation remains dominant during the program implementation phase, whereas involvement in decision making and evaluation is not yet optimal. This study found that social proximity has a dual impact: it enhances participation while simultaneously potentially creating network exclusivity and information access disparities.